Diseño y construcción de una máquina horizontal para procesar esterilla de caña guadua (Angustifolia kunth), en el cantón Quevedo, provincia de Los Ríos año 2014. - Lozano Granda, Eder Ignacio (2015)
The development of this research is the design and construction of a machine to facilitate the process of developing chopped cane , in order to optimize resources and oriented platemaking for - living constructions of " cane " . In order to verify the current status of the reed plate production in previous years in relation to the current year has resulted in accidents , as based on the observation is able to determine which were raised this kind of " tragedies " inside when performing the work since its development has always been the traditional way, workers despite this they perform their jobs , on account of that result play a little production work . As a result of this evaluation is interpreted on the production of those tasks that do not favor a , on medium-high development and manufacturing with less , take the initiative to build the aforementioned machine semiautomatic which they allows to expand their opportunities and capabilities to produce more in a minimum of time.